2019
DOI: 10.1007/s00064-019-0605-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulares Kniearthrodesesystem TITAN (KAM-TITAN) nach fehlgeschlagener Knieendoprothetik

Abstract: Die folgenden vier Originalarbeiten liegen der kumulativen Habilitationsschrift zu Grunde, welche die wesentlichen Ergebnisse der Publikationen zusammenfasst und diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Knee Score range 38-39.2 and WOMAC score was 55.8 [20][21][22]. The functional outcomes and subjective measurements of pain in our patient group are comparable to these results.…”
Section: Discussionsupporting
confidence: 82%
“…Knee Score range 38-39.2 and WOMAC score was 55.8 [20][21][22]. The functional outcomes and subjective measurements of pain in our patient group are comparable to these results.…”
Section: Discussionsupporting
confidence: 82%
“…Since knee arthrodesis is considered a salvage method due to the loss of range of motion, some items in this questionnaire are presumably negatively affected. Gathen et al evaluated a cohort of modular knee arthrodesis after failed revision TKA, and found a mean OKS score of 39.2 [6]. Friedrich et al had a mean OKS score of 38 in their study of two stage arthrodesis of a modular intramedullary nail after septic TKA failure [5].…”
Section: Discussionmentioning
confidence: 99%
“…The indications for knee arthrodesis are limb salvage after failed TKA revision surgery, deficient extensor mechanism and high functional demand in young patients, poor soft tissue coverage, and severe infections with highly virulent microorganisms that preclude joint reconstruction with arthroplasty implants [4]. Several techniques for knee arthrodesis have been described: external fixation, intramedullary nailing, plate fixation, and modular intramedullary implants [5][6][7][8]. Modular segmental implants allow immediate weight bearing without the need of bony fusion, and minimize leg length discrepancy (LLD).…”
Section: Introductionmentioning
confidence: 99%
“…74 Modular IM arthrodesis nails have shown similar functional outcome, pain reduction and infection control results as biologic fixation while minimizing LLD at 30-month follow-up. 75 After a failed two-stage revision, knee arthrodesis presents the treatment most likely to yield the highest expected quality of life. 76…”
Section: Salvage Proceduresmentioning
confidence: 99%